Integration Tree and the Interconnectivity of Science and Religion - Azhar Arsyad (Universitas Darussalam Gontor, 2016)
This article is a kind of introductory explanation of how Islamic epistemology does not and cannot separate religion from the general knowledge and science in general. The idea will begin from the anxiety of some prominent people in religions of the world on the facts happening nowadays at western universities and higher-education institutions. Based on that, this article tries to introduce the classification of knowledge as far as Islam is concerned. It will be elaborated that by recognizing the senses alone, western scientists are only developing a research method, the observation method, or sensory experiments. This observation method is further developed to a very sophisticated method, but it still empties into the absorption of sense-perception. Sense process in the form of reasoning is used, but only to choose, to decide and to reason, not as another instrument in capturing realities. Contrary to Western scientists, as can be seen further, Muslim scientists recognize that the legitimacy of science is not based only on the observation method, but also rational and intuitive methods. In other words, the science does not only recognize the sensory perception in the process of knowledge, but also the sense and perception of the voice of the heart. This has brought about changes and inventions in many fields of knowledge in the early development of Islam. The dichotomy and separation of religion from the general knowledge in Islam as far as history proved had made Islam fail to shine until the time being.